Method for preparing functionalized polymer based on macro-micro reactor chemical-enzyme method

By coupling enzyme-catalyzing the ester exchange reaction and Cu(0)-mediated controlled radical polymerization by Cu(0) in a macromicro reactor, the problems of difficulty in enzyme recovery and long reaction time in traditional reactors are solved, and efficient and controllable preparation of functionalized polyacrylates are achieved.

CN119859212AActive Publication Date: 2025-04-22NANJING TECH UNIV

Patent Information

Application Number
CN202510121540.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-18
Filing Date
2025-01-26
Publication Date
2025-04-22
Estimated Expiration
2045-01-26

AI Technical Summary

Technical Problem

Traditional kettle reactors have problems such as difficulty in enzyme recovery, easy inactivation, too long reaction time and poor reaction controllability in enzyme-catalyzed ester exchange reaction and controlled radical polymerization.

Method used

The chemical-enzymatic coupling reaction based on the macromicroreactor is used to perform a transesterification reaction with a controlled radical polymerization mediated by Cu(0) by a mixture of acrylate monomers, initiators, ligands, functional alcohols and solvents in the macromicroreactor, and the reaction conditions are regulated to achieve efficient preparation of functionalized polyacrylates.

Benefits of technology

The enzymatic ester exchange and polymerization reaction time is significantly shortened, the conversion rate is improved, and high-throughput synthesis is achieved. The characteristic scale of the macromicro reactor can reach the centimeter level, supporting the preparation of functionalized polymers with narrow distribution and controllable structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859212A_ABST
    Figure CN119859212A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a functionalized polymer based on a macro-micro reactor chemical-enzyme method, which comprises the following steps: reacting a mixed solution of an acrylate monomer, an initiator, a ligand, a functional alcohol and a solvent in a micro reactor to obtain a reaction solution containing functionalized polyacrylate, and the micro reactor comprises the macro-micro reactor containing a copper internal member. In a macro-micro reactor, enzymatic ester exchange and Cu (0)-RDRP coupling reaction are carried out to obtain poly (methyl) acrylate with a series of chemical structures and copolymers of the poly (methyl) acrylate. The method is wide in applicable substrate range, and compared with a traditional synthesis method, the macro-micro reactor containing the internal component can remarkably shorten the polymerization time, secondary purification of the monomer is avoided, and the conversion rate is greatly increased. The characteristic scale of the macro-micro reactor reaches centimeter level, and high-flux synthesis can be realized. The invention provides a technical scheme for the preparation of the functionalized poly (methyl) acrylate polymer, and has an industrial conversion prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer synthesis, and in particular to a method for preparing functionalized polymers based on a macro-microreactor chemical-enzyme method. Background Art

[0002] This section merely provides background information related to the present disclosure and is not necessarily prior art.

[0003] Functionalized polyacrylates are an important class of polymer materials that can be used to prepare products with excellent properties such as heat resistance, water resistance, and UV resistance. For example, new functionalized acrylates can be used in industry to synthesize high-performance polymers, coatings, adhesives, and other chemicals, and to manufacture materials that are chemically resistant, high-strength, and highly transparent. In pharmaceutical chemistry, they are used to manufacture sustained-release drug systems to control the release rate and duration of drugs, improve drug therapeutic effects, and reduce adverse reactions. In biology and biomedicine, biosensors, biochips, and biomedical materials can be manufactured. Traditional chemical preparation uses transition metals as catalysts to catalyze ester exchange reactions, which are introduced in situ into ATRP polymerizations to polymerize different monomers step by step to obtain polymers.

[0004] Enzymatic method is one of the green methods for preparing functionalized acrylates. Coupling enzymatic method with chemical catalysis can efficiently prepare functionalized polyacrylates. For example, by combining enzymatic ester exchange monomer synthesis and light-controlled polymerization technology, high monomer conversion rate (~100%) and good end group integrity (>80%) are achieved through photoinduced-reversible addition-fragmentation chain transfer polymerization (PET-RAFT). Different multi-block copolymers are quickly synthesized by continuously adding monomers without purification steps. Not only can products with complex structures and functions be obtained efficiently and conveniently, but also the synthesis steps are simplified and the synthesis cost is reduced, which embodies the concept of green chemistry and sustainable development. It has attracted more and more attention from the chemical and industrial communities. In the use of traditional intermittent reactors, there will be a series of problems such as vigorous stirring that causes enzyme inactivation and low conversion rate. How to improve the yield and increase the reuse of enzymes has become a new challenge.

[0005] Enzymes are regarded as green and efficient catalysts with high chemical selectivity, regioselectivity and stereoselectivity in the reaction process. Candida antarctica lipase A (CALB) is a lipase derived from Candida antarctica, and its commercial name is Novozyme 435. Due to its excellent selectivity, thermal stability and catalytic activity, it is widely used in catalyzing transesterification, ring-opening polymerization, esterification and polycondensation reactions.

[0006] Copper(0)-mediated reversible-deactivated radical polymerization (RDRP) is an active radical polymerization with Cu(0) as the sole catalyst. It has the advantages of simple and mild reaction conditions and rapid polymerization of acrylates. It is used to prepare small molecule homopolymers, block copolymers, complex structure polymers, functional polymers, functionalized surfaces and bioconjugation of various structures. Metallic Cu(0) exists in the form of wire or powder, and the reaction rate can be adjusted by changing the surface area. After polymerization, unused Cu(0) can be removed from the polymer solution and reused in new reactions. In recent years, Cu(0)-mediated RDRP (Cu(0)-RDRP) in continuous flow microreactors has received increasing attention, greatly promoting the possibility of industrial applications.

[0007] In traditional batch reactors, enzyme-catalyzed ester exchange reactions are orthogonal to controlled free radical polymerization reactions, and functionalized polyacrylates can be prepared by a "one-pot method". However, they face problems such as difficulty in enzyme recovery, easy inactivation, long reaction time, and poor reaction controllability.

[0008] By introducing a microreactor, its small size has a high specific surface area to volume ratio, thereby enhancing the transfer of mass and energy, increasing the reaction rate, reducing the diffusion distance and the reactant retention volume, and thus providing advantages for process intensification, and can overcome the problems of long reaction time faced by kettle reactors, but the yield still needs to be improved. The present invention is based on a macro-microreactor for chemical-enzymatic coupling reaction, greatly shortening the enzymatic ester exchange and polymerization reaction time, and successfully improving the conversion rate, and the characteristic scale of the macro-microreactor can reach the centimeter level, which can achieve high-throughput synthesis. Summary of the invention

[0009] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing functionalized polymers based on a macro-microreactor chemical-enzymatic method in view of the deficiencies in the prior art.

[0010] Invention concept: The present invention designs a novel macro-microreactor, couples biocatalysis with chemical catalysis and applies it to a microfluidic reaction platform, and efficiently prepares functionalized polyacrylates with narrow distribution and controllable structure by regulating the reaction conditions.

[0011] In order to solve the above technical problems, the present invention discloses the following technical solutions:

[0012] In the first aspect, the present invention discloses a method for preparing functionalized polymers by macro-continuous flow chemistry-enzymatic method, wherein a mixed solution of acrylate monomers, initiators, ligands, functional alcohols and solvents are reacted in a macro-continuous flow chemistry-enzymatic microreactor to obtain a reaction solution containing functionalized polyacrylate.

[0013] In some embodiments, the macro-continuous flow chemical-enzymatic microreactor is a macro-microreactor containing an enzyme; the macro-microreactor contains copper internal components; in some embodiments, it is a traditional continuous flow chemical-enzymatic microreactor, and the traditional continuous flow chemical-enzymatic microreactor is a copper tube.

[0014] In a second aspect, the present invention discloses an application of a macro-microreactor in the preparation of functionalized polymers, wherein a mixed solution of acrylate monomers, initiators, ligands, functional alcohols and solvents is reacted in a microreactor to obtain a reaction solution containing functionalized polyacrylates; the macro-microreactor contains copper internal components.

[0015] In the first and second aspects above,

[0016] The reaction involves a transesterification reaction and a Cu(0)-mediated controlled free radical polymerization simultaneously, specifically:

[0017]

[0018] wherein n and m are independently selected from any number in the range of 5 to 300; R1 is selected from H or methyl; R2 is selected from methyl, butyl, cyclohexyl, benzyl, -CH2CF3; R3 is selected from methyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-hexyl, furfuryl, morpholineethyl, n-undecyl, triethylene glycol methoxy and propionitrile; R4 is selected from ethyl methylpropionate, ethyl phenylacetate, diethyl methylmalonate, ethylene isobutyrate, methyl propionate, ethyl propionate, propionitrile and PHCOCH-; and X is selected from Br or Cl.

[0019] Taking trifluoroethyl acrylate as an example, the reaction process is as follows, wherein trifluoroethyl acrylate is used as a monomer for Cu(0)-mediated controlled radical polymerization and a substrate for enzymatic transesterification, copper is used as a catalyst for the polymerization reaction, and in an enzyme microreactor, the transesterification reaction and the Cu(0)-mediated controlled radical polymerization are carried out simultaneously, the monomer trifluoroethyl acrylate and the functional alcohol in the system are transesterified to generate R acrylate, and trifluoroethyl acrylate and R acrylate simultaneously participate in the polymerization reaction to prepare functionalized polyacrylate, thus exhibiting copolymerization characteristics.

[0020]

[0021] Wherein, x and y are independently selected from any number between 5 and 300; and R is selected from methyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-hexyl, furfuryl, morpholineethyl, n-undecyl, triethylene glycol methoxy and propionitrile.

[0022] The present invention can reduce the rate of enzymatic transesterification by reducing the monomer concentration (increasing the solvent content). For example, when the functional alcohol is n-hexanol, the ratio of polytrifluoroethyl acrylate (PTFEA) and polyn-hexyl acrylate (PHA) is 1 / 1 and PTFEA-co-PHA dominated by PTFEA can be successfully prepared. That is, when the transesterification rate is high, the functionalized polymer structure is dominated by polyacrylate R ester, and when the rate is low, the structure is dominated by polytrifluoroethyl acrylate. Copolymers with different structures can be prepared by one-pot method.

[0023] The monomer is any one or a combination of trifluoroethyl acrylate, methyl methacrylate, trifluoroethyl methacrylate, methyl acrylate, n-butyl acrylate, benzyl acrylate and cyclohexyl acrylate, preferably any one or a combination of trifluoroethyl acrylate, benzyl acrylate and cyclohexyl acrylate, and more preferably trifluoroethyl acrylate.

[0024]

[0025] Wherein, the initiator is any one or a combination of ethyl 2-bromo-2-methylpropionate, ethyl α-bromophenylacetate, diethyl 2-bromo-2-methylmalonate, ethylene glycol bromoisobutyrate, methyl 2-chloropropionate, 2,2-dichloroacetophenone, ethyl 2-chloropropionate and 2-bromopropionitrile, preferably any one or a combination of ethyl 2-bromo-2-methylpropionate and ethyl α-bromophenylacetate, and further preferably ethyl 2-bromo-2-methylpropionate; preferably, the molar ratio of the initiator to the monomer is 1:100 to 1000, such as 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900.

[0026]

[0027] Wherein, the ligand is tris(2-dimethylaminoethyl)amine and / or 4,4'-dinonyl-2,2'-bipyridine, preferably tris(2-dimethylaminoethyl)amine; preferably, the molar ratio of the initiator to the ligand is 1:0.1-1, preferably 1:0.25-0.5, and more preferably 1:0.25.

[0028] Wherein, the functional alcohol is any one or a combination of methanol, n-propanol, isopropanol, n-butanol, tert-butanol, n-hexanol, furfuryl alcohol, undecanol, 2-morpholinoethanol, triethylene glycol monomethyl ether and 3-hydroxypropionitrile; preferably, the molar ratio of the initiator to the functional alcohol is 1:100-1200, such as 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, 1:1000, 1:1100.

[0029]

[0030] Wherein, the solvent is any one or a combination of dimethyl sulfoxide, tetrahydrofuran, N,N-dimethylformamide and toluene, preferably dimethyl sulfoxide; preferably, the concentration of the monomer is 1 to 5 mol / L; the concentration of the monomer = (n 单体 ) / (V 单体 +V 功能化醇 +V 溶剂 ).

[0031] In the present invention, the reaction device is as follows Figure 1 As shown, the reaction is carried out in a reaction device containing a macro continuous flow chemical-enzymatic microreactor (filled with lipase) or a traditional continuous flow chemical-enzymatic microreactor (filled with lipase). The reaction device comprises a feed pump, a syringe, any of the aforementioned microreactors and a receiving device, and the feed pump, the syringe, the microreactor and the receiving device are sequentially connected in series through a pipeline; the microreactor is provided with a heating device; the microreactor is repeatedly flushed with toluene or tetrahydrofuran before each use to purify the pipeline.

[0032] The preparation method of the macro-continuous flow chemical-enzymatic microreactor is as follows: a centrally hollowed copper internal component (with a diameter of 0.5 to 3 mm, such as 0.5 to 1 mm) and an immobilized enzyme are placed in a microchannel tube with an inner diameter of 2 to 15 mm (such as 2 to 4.3 mm); the copper internal component includes a copper spiral. In some embodiments, the copper internal component is a spiral internal component, a serpentine internal component, an O-shaped internal component, or a linear internal component; the spiral internal component, the serpentine internal component, and the O-shaped internal component have a pitch of 0.5 to 10 mm, such as 1 to 3 mm.

[0033] Among them, the conventional continuous flow chemical-enzymatic microreactor is to place the immobilized enzyme into a microchannel tube with an inner diameter of 1 to 4.5 mm, such as 4.3 mm, 4.5 mm; in some embodiments, the microchannel pipe is a copper tube.

[0034] Wherein, the retention volume of the macro-microreactor is 1-20 mL, such as 1, 3, 5, 10, 15 mL.

[0035] Among them, the copper tube and copper spiral need to be activated, and the activation method is: 20mL of dilute sulfuric acid solution is drawn by a syringe, and the pipeline is flushed at a flow rate of 0.333mL / min for 60min. After that, 20mL of distilled water is drawn to flush the pipeline at a flow rate of 4mL / min for 5min to remove Cu2O and CuO on the copper surface, and 20mL of trifluoroethanol is drawn again, and the pipeline is flushed at a flow rate of 0.333mL / min for 60min. Finally, the continuous flow reactor is dried under N2 atmosphere to minimize oxygen in the system.

[0036] The loading amount of the immobilized enzyme in the microchannel pipeline is controlled to be 0.3-1 g / mL, such as 0.3, 0.5, 0.6, and 0.8 g / mL; fresh enzyme is added before each use and the two ends of the tube are fixed with a small amount of cotton, and the enzyme is taken out after the end.

[0037] Wherein, the immobilized enzyme is an immobilized lipase, such as any one or a combination of Candida antarctic lipase B (CALB), Candida rugosa lipase, Amano Lipase from Pseudomonas fluorescens and lipase PS from Burkholderia cepacia (LPS), preferably Candida antarctic lipase B (CALB), i.e., immobilized Novozymes 435 lipase, with an enzyme activity of 10000 PLU / g.

[0038] The mixed solution is prepared by mixing acrylate monomers, initiators, ligands, functional alcohols and solvents under the protection of an inert gas; the mixed solution is reacted after removing dissolved oxygen; preferably, the method of removing dissolved oxygen is bubbling or liquid nitrogen freezing-vacuuming-dissolving.

[0039] Wherein, the reaction temperature is 0-100°C, such as 40°C, 60°C.

[0040] Wherein, the reaction rate is 0.0033-25 mL / min, such as 0.0067-0.5 mL / min.

[0041] Wherein, the retention time of the reaction is 2 to 300 min, such as 10 to 300 min, preferably 10 to 150 min.

[0042] Wherein, after the reaction is completed, the reaction solution is quenched, an organic precipitant is added, and centrifuged to obtain a solid functionalized polyacrylate; preferably, the quencher is liquid nitrogen; preferably, the organic precipitant is a mixed solution of methanol and water, methanol, or n-hexane. In some embodiments, the temperature of the organic precipitant is -20°C; the amount of the organic precipitant is 20 to 100 times the volume of the reaction solution; preferably, after 2 hours of precipitation, centrifugation is performed; more preferably, the substance obtained by centrifugation is dissolved in toluene or tetrahydrofuran, and then an organic precipitant is added for precipitation, and the step is repeated three times for purification; the purified product solid is vacuum dried.

[0043] After the reaction is completed, the solid functionalized polyacrylate obtained by the reaction of different monomer concentrations has a controllable sequence structure. The purified functionalized acrylate polymer has three predictable structures. Specifically, the reaction of high-concentration monomers will obtain a product mainly composed of newly generated acrylates, the reaction of lower-concentration monomers will obtain a product composed of trifluoroethyl acrylate and new monomers with a polymerization degree of approximately 1:1, and the reaction of low-concentration monomers can obtain a polymerization product mainly composed of trifluoroethyl acrylate.

[0044] In the present invention, a copper internal component and an enzyme are placed in a microchannel to form a macro-micro reactor, and a mixed solution of acrylate monomers, initiators, ligands, functional alcohols and solvents are reacted in the macro-micro reactor to obtain functionalized polyacrylate. The polymerization reaction rate in the macro-micro reactor containing the copper internal component provided by the present invention is better than that of the copper tube, and even better than that of the copper powder. The present invention couples the copper-catalyzed controlled free radical polymerization with the enzymatic transesterification reaction, and the two do not interfere with each other, realizing chemical-enzymatic coupling, and the enzyme catalysis rate can be controlled by changing the solvent concentration, thereby efficiently preparing a narrowly distributed and structurally controllable functionalized acrylate copolymer.

[0045] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0046] (1) The present invention is based on macro-microreactor-enhanced chemical-enzymatic coupling reaction process to rapidly and high-throughput prepare a series of chemical structure poly(meth)acrylate copolymers.

[0047] (2) Compared with the traditional autoclave reactor, the present invention significantly improves the polymerization conversion rate and reduces the molecular weight distribution index based on the macro-micro reactor. For example, when trifluoroethyl acrylate and n-hexanol react for the same reaction time of 60 min, the polymerization conversion rate is increased from 23.08% to 63.23%, and the molecular weight distribution index is reduced from 1.42 to 1.14.

[0048] (3) Compared with a typical microreactor (characteristic scale = 1.0 mm), the present invention significantly increases the reaction flux based on the macro-microreactor, for example, the flow rate is increased from 0.006667 ml / min to 0.01667 ml / min, and the output per unit time is increased from 0.0292 g / min to 0.0445 g / min.

[0049] (4) Compared with the continuous flow reactor (>2.0 mm without internal components), the present invention significantly improves the conversion rate and reduces the distribution index based on the macro-micro reactor. For example, under the same reaction time, the polymerization conversion rate is increased from 44.79% to 63.23%, and the distribution index is reduced from 1.22 to 1.14. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0051] Figure 1 Schematic diagram of the macro-microreactor system used in this experiment.

[0052] Figure 2 The functionalized poly(trifluoroethyl acrylate)-poly(n-hexyl acrylate) copolymer of Example 1 1 H NMR spectra.

[0053] Figure 3 Example 4 functionalized poly(trifluoroethyl acrylate)-poly(methyl acrylate) copolymer 1 H NMR spectra.

[0054] Figure 4 Example 6 functionalized polymethyl acrylate-poly(n-hexyl acrylate) copolymer 1 H NMR spectra.

[0055] Figure 5 Example 12 functionalized poly(trifluoroethyl acrylate)-poly(morpholine ethyl acrylate) copolymer 1 H NMR spectra.

[0056] Figure 6 Example 14 functionalized polymethyl acrylate-polyundecyl acrylate copolymer 1 H NMR spectra.

[0057] Figure 7 Example 15 functionalized poly(trifluoroethyl acrylate)-poly(acrylonitrile acrylate) copolymer 1 H NMR spectra. DETAILED DESCRIPTION

[0058] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0059] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0060] In the following examples, the number average molecular weight and molecular weight distribution of the products were measured using the following methods.

[0061] A Wyatt size exclusion chromatography system was used with tetrahydrofuran as the mobile phase, a flow rate of 0.7 mL / min, a column temperature of 35°C, and an injection volume of 0.4 mL.

[0062] Sample measurement: Take 2 mg of pure sample in a centrifuge tube, add 1 mL of tetrahydrofuran solution to dilute, and then filter with a disposable filter head (containing a 0.33 m organic filter membrane) and take 0.4 mL of solution for sampling.

[0063] A 400 MHz Bruker NMR instrument was used to 1 H NMR and 13 C NMR was used to characterize the structure of the polymerized product. Take 10 mg of the sample and put it into a NMR tube, add deuterated chloroform, shake it until it is completely dissolved, and then measure the sample.

[0064] In the following examples, the Candida antarctic lipase B (CALB) used has a particle size of 0.3-0.9 mm and an enzyme activity of 10,000 PLU / g. The purchaser is Nanjing Deming Chemical Technology Co., Ltd. Porcine pancreatic lipase (Lipase (pocine pancreas)) has an enzyme activity of 30,000 U / g. The purchaser is Shanghai Yuanye Biotechnology Co., Ltd. Lipase from Candida rugosa has an enzyme activity of 700 U / mg. The purchaser is Shanghai Yuanye Biotechnology Co., Ltd. Amano Lipase from Pseudomonasfluorescens has an enzyme activity of 20,000 U / g. The purchaser is Merck. Lipase PS from Burkholderia cepacia (LPS) has an enzyme activity of 23,000 U / mg. The purchaser is Shanghai McLean Biochemical Technology Co., Ltd.

[0065] The following examples are all carried out in a macro-microreactor system. Figure 1 As shown, the macro-microreactor is made: in the macro-microreactor HSI (D-d4-l3), D represents the inner diameter of the reactor (mm), d4 represents the diameter of the spiral wire (mm), and l3 represents the pitch (mm). There are 4 types, macro-microreactor SLSI (D-d1), SSI (D-d2-l1), OSI (D-d3-l2), and the macro-microreactor SLSI (D-d1) does not involve the pitch.

[0066] The following embodiments involve two reactions, namely, an enzymatic transesterification reaction and a Cu(0)-mediated controlled free radical polymerization. The two reactions proceed simultaneously without affecting each other, and the new monomers produced by the enzymatic transesterification can be provided to the polymerization reaction for polymerization.

[0067] The enzyme-catalyzed transesterification conversion rate and Cu(0)-catalyzed polymerization conversion rate described in the following examples are calculated by the quenched liquid hydrogen spectrum of the reaction, and the degree of transesterification and polymerization reaction is calculated by the integral ratio of the corresponding characteristic peaks. Specifically, taking Example 1 as an example, the enzyme-catalyzed transesterification conversion rate = n-hexyl acrylate peak integral / (n-hexyl acrylate integral + trifluoroethyl acrylate integral) * 100%; Cu(0)-catalyzed polymerization conversion rate = (poly-n-hexyl acrylate peak + poly-trifluoroethyl acrylate peak) / (poly-n-hexyl acrylate peak + poly-trifluoroethyl acrylate peak + n-hexyl acrylate peak + trifluoroethyl acrylate peak) * 100%.

[0068] Example 1

[0069] 0.6 g of CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor HSI (4.3-1-3) (retention volume was 1.00 mL). The pipeline was flushed with toluene solvent after redispersion and drying. 9.631 g (62.5 mmol) of trifluoroethyl acrylate, 6.385 g (62.5 mmol) of n-hexanol, 0.061 g (0.3125 mmol) of ethyl 2-bromo-2-methylpropionate, 0.018 g (0.078 mmol) of tris(2-dimethylaminoethyl)amine and dimethyl sulfoxide (0.14 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.01667 mL / min, i.e., the residence time was 60 min. The reaction temperature was 40°C, the reaction was started, and the reaction solution was collected after 120 minutes. While collecting, it was quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours. The precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 97.74%, and the Cu(0)-catalyzed polymerization conversion rate was 63.23%. The obtained poly(trifluoroethyl acrylate)-poly(n-hexyl acrylate) copolymer (PTFEA 10 -co-PHA 66 ) has a number average molecular weight of 12230 g / mol ( Figure 2 ), the molecular weight distribution index is 1.14, and the output per minute is 0.0445 g / min.

[0070] Example 2

[0071] 0.6 g of CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor SSI (4.3-1-3) (retention volume of 1.00 mL). The pipeline was flushed with toluene solvent after redispersion and drying. 10.506 g (62.5 mmol) of trifluoroethyl methacrylate, 10.769 g (62.5 mmol) of undecanol, 0.066 g (0.3125 mmol) of ethylene glycol bromoisobutyrate, 0.018 g (0.078 mmol) of tris(2-dimethylaminoethyl)amine and N,N-dimethylformamide (4.11 mL) were added to a 50 mL Schlenk round-bottom flask to make a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.0111 mL / min, that is, the residence time was 90 min. The reaction temperature was 40°C, and the reaction was started. After 180 minutes, the reaction solution was collected and quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours. The precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 82.6%, and the Cu(0)-catalyzed polymerization conversion rate was 35.82%. The obtained poly(trifluoroethyl methacrylate)-poly(undecyl methacrylate) copolymer (PTFEMA) 13 -co-PX 59 ) has a number average molecular weight of 7300 g / mol, a molecular weight distribution index of 1.19, and a minute output of 0.0342 g / min.

[0072] Example 3

[0073] 1.8 g of CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor OSI (4.3-1-3) (retention volume was 3.00 mL). The pipeline was flushed with toluene solvent after redispersion and drying. 6.257 g (62.5 mmol) of methyl methacrylate, 4.633 g (62.5 mmol) of n-butanol, 0.079 g (0.3125 mmol) of diethyl 2-bromo-2-methylmalonate, 0.032 g (0.078 mmol) of 4,4'-dinonyl-2,2'-bipyridine and tetrahydrofuran (1.15 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed using the Schlenk anhydrous and oxygen-free technique. It was transferred into a syringe and the injection pump flow rate was set to 0.0333 mL / min, that is, the residence time was 90 min. The reaction temperature was 40°C, and the reaction was started. After 180 minutes, the reaction liquid was collected and quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours. The precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 26.15%, and the Cu(0)-catalyzed polymerization conversion rate was 40.15%. The obtained polymethyl methacrylate-polybutyl methacrylate copolymer (PMMA 61 -co-PX 21 ) has a number average molecular weight of 10570 g / mol, a molecular weight distribution index of 1.31, and a minute output of 0.0331 g / min.

[0074] Example 4

[0075] 0.6 g of CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor HSI (4.3-1-3) (retention volume was 1.00 mL). The pipeline was flushed with toluene solvent after redispersion and drying. 4.815 g (31.25 mmol) of trifluoroethyl acrylate, 1.002 g (31.25 mmol) of methanol, 0.061 g (0.3125 mmol) of ethyl 2-bromo-2-methylpropionate, 0.018 g (0.078 mmol) of tris(2-dimethylaminoethyl)amine and dimethyl sulfoxide (1.025 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed using the Schlenk anhydrous and oxygen-free technique. It was transferred into a syringe and the flow rate was set to 0.0333 mL / min, i.e., the residence time was 30 min. The reaction temperature was 40°C, and the reaction was started. After 60 minutes, the reaction solution was collected and quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours. The precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 97.0%, and the Cu(0)-catalyzed polymerization conversion rate was 21.93%. The obtained poly(trifluoroethyl acrylate)-poly(methyl acrylate) copolymer structure (PTFEA8-co-PMA 32 ) has a number average molecular weight of 4250 g / mol ( Figure 3 ), the molecular weight distribution index is 1.36, and the output per minute is 0.0398g / min.

[0076] Example 5

[0077] 2.4 g CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor HSI (8-3-1) (retention volume was 4.00 mL). The pipeline was rinsed with toluene solvent after redispersion and drying. 10.137 g (62.5 mmol) benzyl acrylate, 2.003 g (62.5 mmol) methanol, 0.076 g (0.3125 mmol) ethyl α-bromophenylacetate, 0.018 g (0.078 mmol) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (3.715 mL) were added to a 50 mL Schlenk round-bottom flask to make a solution, and the dissolved oxygen in the solvent was removed using the Schlenk anhydrous and oxygen-free technique. It was transferred into a syringe and the injection pump flow rate was set to 0.13333 mL / min, that is, the residence time was 30 min. The reaction temperature was 40 ° C, the reaction was started, and the reaction solution was collected after 60 min. While collecting, it was quenched in liquid nitrogen. After the collection is completed, 90 mL of cold methanol is added and allowed to stand for 2 hours, and the precipitate is separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps are repeated three times in total, and the product is placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate is measured to be 85.23%, and the Cu(0)-catalyzed polymerization conversion rate is 48.37%. The obtained polybenzyl acrylate-polymethyl acrylate copolymer (PX 28 -co-PMA 71 ) has a number average molecular weight of 12670 g / mol, a molecular weight distribution index of 1.28, and a minute output of 0.0119 g / min.

[0078] Example 6

[0079] 3.0g CALB with a particle size of 0.3-0.9mm was filled into the macro-microreactor HSI (10-3-3) (retention volume was 5.00mL). The pipeline was rinsed with toluene solvent after redispersion and drying. 5.380g (62.5mmol) methyl acrylate, 6.385g (62.5mmol) n-hexanol, 0.061g (0.3125mmol) ethyl 2-bromo-2-methylpropionate, 0.018g (0.078mmol) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (2.15mL) were added to a 50mL Schlenk round-bottom flask to make a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.5mL / min, that is, the residence time was 10min. The reaction temperature was 60°C, and the reaction was started. After 20min, the reaction solution was collected and quenched in liquid nitrogen while being collected. After the collection is completed, 90 mL of cold methanol is added and allowed to stand for 2 hours, and the precipitate is separated by centrifugation. It is dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps are repeated three times in total, and the product is placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate is measured to be 47.9%, and the Cu(0)-catalyzed polymerization conversion rate is 43.29%. The obtained polymethyl acrylate-poly(n-hexyl acrylate) copolymer (PMA 58 -co-PHA 26 )The number average molecular weight is 11580g / mol( Figure 4 ), the molecular weight distribution index is 1.21, and the output per minute is 0.0326g / min.

[0080] Example 7

[0081] 0.6 g CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor HSI (3-1-10) (retention volume was 1.00 mL). The pipeline was rinsed with toluene solvent after redispersion and drying. 8.01 g (62.5 mmol) of n-butyl acrylate, 7.013 g (62.5 mmol) of tert-butyl alcohol, 0.043 g (0.3125 mmol) of ethyl 2-chloropropionate, 0.018 g (0.078 mmol) of tris (2-dimethylaminoethyl) amine and toluene (4.20 mL) were added to a 50 mL Schlenk round-bottom flask to make a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.01667 mL / min, that is, the residence time was 60 min. The reaction temperature was 60 ° C, and the reaction was started. After 120 min, the reaction solution was collected and quenched in liquid nitrogen while being collected. After the collection is completed, 90 mL of cold methanol is added and allowed to stand for 2 hours, and the precipitate is separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps are repeated three times in total, and the product is placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate is measured to be 31.25%, and the Cu(0)-catalyzed polymerization conversion rate is 27.8%. The obtained poly(n-butyl acrylate-poly(tert-butyl acrylate) copolymer (PX 31 -co-PX 24 ) has a number average molecular weight of 7100 g / mol, a molecular weight distribution index of 1.54, and a minute output of 0.0163 g / min.

[0082] Example 8

[0083] 1.2 g CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor SSI (3-1-8) (retention volume was 2.00 mL). The pipeline was rinsed with toluene solvent after redispersion and drying. 9.638 g (62.5 mmol) cyclohexyl acrylate, 3.756 g (62.5 mmol) isopropanol, 0.041 g (0.3125 mmol) 2-bromopropionitrile, 0.018 g (0.078 mmol) tris (2-dimethylaminoethyl) amine and N, N-dimethylformamide (5.18 mL) were added to a 50 mL Schlenk round-bottom flask to make a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.013333 mL / min, that is, the residence time was 150 min. The reaction temperature was 0 ° C, the reaction was started, and the reaction solution was collected after 300 min. While collecting, it was quenched in liquid nitrogen. After the collection is completed, 90 mL of cold methanol is added and allowed to stand for 2 hours, and the precipitate is separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps are repeated three times in total, and the product is placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate is measured to be 9.39%, and the Cu(0)-catalyzed polymerization conversion rate is 56.79%. The obtained poly(cyclohexyl acrylate-poly(isopropyl acrylate) copolymer (PX 103 -co-PX 12 ) has a number average molecular weight of 12950 g / mol, a molecular weight distribution index of 1.32, and a minute output of 0.0243 g / min.

[0084] Example 9

[0085] 0.6 g CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor HSI (4.3-1-3) (retention volume was 1.00 mL). The pipeline was flushed with toluene solvent after redispersion and drying. 9.631 g (62.5 mmol) trifluoroethyl acrylate, 6.385 g (62.5 mmol) n-hexanol, 0.061 g (0.3125 mmol) ethyl 2-bromo-2-methylpropionate, 0.018 g (0.078 mmol) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (15.49 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.0067 mL / min, i.e., the residence time was 150 min. The reaction temperature was 40°C, the reaction was started, and the reaction solution was collected after 300 minutes. While collecting, it was quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours, and the precipitate was separated by centrifugation. The tetrahydrofuran was used to dissolve and re-separated according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 12.67%, and the Cu(0)-catalyzed polymerization conversion rate was 35.54%. The obtained poly(trifluoroethyl acrylate)-poly(n-hexyl acrylate) copolymer (PTFEA 63 -co-PHA9) has a number average molecular weight of 12950 g / mol, a molecular weight distribution index of 1.20, and a minute output of 0.0431 g / min.

[0086] Example 10

[0087] 3.0 g of CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor OSI (15-2-3) (retention volume of 5.00 mL). The pipeline was rinsed with toluene solvent after redispersion and drying. 4.005 g (31.25 mmol) of n-butyl acrylate, 5.131 g (31.25 mmol) of triethylene glycol monomethyl ether, 0.059 g (0.3125 mmol) of 2,2-dichloroacetophenone, 0.018 g (0.078 mmol) of tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (0.94 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.16667 mL / min, i.e., the residence time was 30 min. The reaction temperature was 40°C, the reaction was started, and the reaction solution was collected after 60 minutes. While collecting, it was quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours, and the precipitate was separated by centrifugation. The tetrahydrofuran was used to dissolve and the precipitate was separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 7.87%, and the Cu(0)-catalyzed polymerization conversion rate was 38.10%. The obtained polybutyl acrylate-polytrimethyl ether acrylate copolymer (PX 65 -co-PX2) has a number average molecular weight of 8010 g / mol, a molecular weight distribution index of 1.69, and a minute output of 0.0751 g / min.

[0088] Embodiment 11

[0089] 0.6 g CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor OSI (2-0.5-5) (retention volume of 1.00 mL). The pipeline was flushed with toluene solvent after redispersion and drying. 9.638 g (62.5 mmol) cyclohexyl acrylate, 6.125 g (62.5 mmol) furfuryl alcohol, 0.038 g (0.3125 mmol) methyl 2-chloropropionate, 0.018 g (0.078 mmol) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (0.325 mL) were added to a 50 mL Schlenk round-bottom flask to make a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.00833 mL / min, that is, the residence time was 120 min. The reaction temperature was 40°C, the reaction was started, and the reaction solution was collected after 240 minutes. While collecting, it was quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours, and the precipitate was separated by centrifugation. The tetrahydrofuran was used to dissolve and the precipitate was separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 75.23%, and the Cu(0)-catalyzed polymerization conversion rate was 21.83%. The obtained polycyclohexyl acrylate-polyfurfuryl acrylate copolymer (PX 17 -co-PX 40 ) has a number average molecular weight of 9530 g / mol, a molecular weight distribution index of 1.35, and a minute output of 0.0239 g / min.

[0090] Example 12

[0091] 1.8 g CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor HSI (6-0.5-10) (retention volume of 3.00 mL) and the pipeline was flushed with toluene solvent after redispersion and drying. 9.632 g (62.5 mmol) trifluoroethyl acrylate, 8.19 g (62.5 mmol) 2-morpholineethanol, 0.061 g (0.3125 mmol) ethyl 2-bromo-2-methylpropionate, 0.018 g (0.078 mmol) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (0.135 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.05 mL / min, i.e., the residence time was 60 min. The reaction temperature was 40°C, the reaction was started, and the reaction solution was collected after 120 minutes. While collecting, it was quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours. The precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 92.53%, and the Cu(0)-catalyzed polymerization conversion rate was 58.03%. The obtained poly(trifluoroethyl acrylate)-poly(morpholine ethyl acrylate) copolymer (PTFEA 23 -co-PX 95 ) has a number average molecular weight of 19530 g / mol ( Figure 5 ), the molecular weight distribution index is 1.21, and the output per minute is 0.0915 g / min.

[0092] Embodiment 13

[0093] 0.6 g of CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor HSI (4.3-1-3) (retention volume was 1.00 mL). The pipeline was flushed with toluene solvent after redispersion and drying. 9.631 g (62.5 mmol) of trifluoroethyl acrylate, 6.385 g (62.5 mmol) of n-hexanol, 0.061 g (0.3125 mmol) of ethyl 2-bromo-2-methylpropionate, 0.018 g (0.078 mmol) of tris(2-dimethylaminoethyl)amine and dimethyl sulfoxide (6.56 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.0111 mL / min, i.e., the residence time was 90 min. The reaction temperature was 40°C, the reaction was started, and the reaction solution was collected after 180 minutes. While collecting, it was quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours. The precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 23.07%, and the Cu(0)-catalyzed polymerization conversion rate was 61.06%. The obtained poly(trifluoroethyl acrylate)-poly(n-hexyl acrylate) copolymer (PTFEA 55 -co-PHA 45 ) has a number average molecular weight of 16640 g / mol, a molecular weight distribution index of 1.23, and a minute output of 0.0708 g / min.

[0094] Embodiment 14

[0095] 0.6 g CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor SLSI (4.3-1) (retention volume was 1.00 mL). The pipeline was rinsed with toluene solvent after redispersion and drying. 5.380 g (62.5 mmol) methyl acrylate, 10.769 g (62.5 mmol) undecyl alcohol, 0.061 g (0.3125 mmol) ethyl 2-bromo-2-methylpropionate, 0.018 g (0.078 mmol) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (2.0 mL) were added to a 50 mL Schlenk round-bottom flask to make a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.01667 mL / min, that is, the residence time was 60 min. The reaction temperature was 40 ° C, the reaction was started, and the reaction solution was collected after 120 min. While collecting, it was quenched in liquid nitrogen. After the collection is completed, 90 mL of cold methanol is added and allowed to stand for 2 hours, and the precipitate is separated by centrifugation. It is dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps are repeated three times in total, and the product is placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate is measured to be 63.20%, and the Cu(0)-catalyzed polymerization conversion rate is 35.61%. The obtained polymethyl acrylate-poly(undecyl acrylate) copolymer (PMA 40 -co-PX 32 ) has a number average molecular weight of 9640 g / mol ( Figure 6 ), the molecular weight distribution index is 1.22, and the output per minute is 0.0471 g / min.

[0096] Embodiment 15

[0097] 1.2 g CALB with a particle size of 0.3 to 0.9 mm was filled into the macro-microreactor HSI (4.3-1-3) (retention volume was 2.00 mL). The pipeline was flushed with toluene solvent after redispersion and drying. 9.631 g (62.5 mmol) trifluoroethyl acrylate, 4.442 g (62.5 mmol) 3-hydroxypropionitrile, 0.061 g (0.3125 mmol) ethyl 2-bromo-2-methylpropionate, 0.018 g (0.078 mmol) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (3.435 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.0222 mL / min, i.e., the residence time was 90 min. The reaction temperature was 40°C, and the reaction was started. After 180 minutes, the reaction solution was collected and quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours. The precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 86.32%, and the Cu(0)-catalyzed polymerization conversion rate was 42.33%. The obtained poly(trifluoroethyl acrylate)-poly(acrylic acid nitrile) copolymer (PTFEA 24 -co-PX 67 ) has a number average molecular weight of 14740 g / mol ( Figure 7 ), the molecular weight distribution index is 1.27, and the output per minute is 0.0506g / min.

[0098] Example 16

[0099] A copper spiral internal component is made by winding a 1mm diameter stainless steel wire evenly and tightly around the central axis with a 3mm pitch as the standard. The internal component is placed in a microchannel with an inner diameter of 4.3mm and activated. 0.6g of immobilized enzyme Novozyme435 with a particle size of 0.3-0.9mm is filled into the activated copper spiral internal component microreactor (retaining a volume of 1.00mL), and the two ends of the tube are fixed with a small amount of cotton. A microchannel tube with an inner diameter of 1mm is used to connect the syringe and the new microreactor (retaining a volume of 0.5mL), and a microchannel reactor with an inner diameter of 1mm is used to connect the new microreactor and the receiving device (retaining a volume of 0.5mL). The pipeline is rinsed with toluene solvent after redispersion and drying. In a 50mL Schlenk round-bottom flask, add 62.5mmol (9.631g) trifluoroethyl acrylate (7.92mL), 62.5mmol (2.003g) methanol (2.53mL), 0.3125mmol (0.061g) ethyl 2-bromo-2-methylpropionate, 0.078mmol (0.018g) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (2.05mL) to make a solution, and remove the dissolved oxygen in the solvent by bubbling. Move it into the syringe of the injection device, set the flow rate to 0.01111mL / min, the reaction temperature to 0℃, start the reaction, collect the reaction solution after 90min, and quench it in liquid nitrogen while collecting. After the collection is completed, add 90mL of cold methanol and let it stand for 2h, centrifuge and separate the precipitate, dissolve it with tetrahydrofuran and separate it again according to the above precipitation. Repeat the separation and purification steps three times in total, and the product is placed in a vacuum drying oven and dried for 48h. The structure of the obtained poly(trifluoroethyl acrylate)-poly(methyl acrylate) copolymer is 1 H NMR and GPC identification showed that the enzyme-catalyzed transesterification conversion rate was 97.74%, and the Cu(0)-catalyzed polymerization conversion rate was 58.01%. GPC determination showed that the polymer number average molecular weight was 12400 g / mol, and the molecular weight distribution index was 1.21.

[0100] Comparative Example 1

[0101] In a 50mL Schlenk round-bottom flask, 9.631g (62.5mmol) trifluoroethyl acrylate, 6.385g (62.5mmol) n-hexanol, 0.061g (0.3125mmol) ethyl 2-bromo-2-methylpropionate, 0.018g (0.078mmol) tris(2-dimethylaminoethyl)amine, 40mg copper powder, 0.6g Novozyme immobilized lipase and dimethyl sulfoxide (0.135mL) were added to make a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. The reaction temperature was 40°C, and the reaction was started. After 60min of reaction, it was quenched in liquid nitrogen. At the same time, 90mL of cold methanol was added and allowed to stand for 2h, and the precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times, and the obtained product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was 74.97%, and the Cu(0)-catalyzed polymerization conversion rate was 23.08%. The obtained poly(trifluoroethyl acrylate-poly(n-hexyl acrylate) copolymer (PTFEA 15 -co-PHA 32 ) has a number average molecular weight of 8160 g / mol and a molecular weight distribution index of 1.42.

[0102] Comparative Example 2

[0103] 0.6 g of immobilized enzyme Novozyme435 with a particle size of 0.3 to 0.9 mm was filled into an activated copper tube microreactor with an inner diameter of 1 mm (retained volume 1.00 mL). The pipeline was rinsed with toluene solvent after redispersion and drying. 9.632 g (62.5 mmol) of trifluoroethyl acrylate, 6.385 g (62.5 mmol) of n-hexanol, 0.061 g (0.3125 mmol) of ethyl 2-bromo-2-methylpropionate, 0.018 g (0.078 mmol) of tris(2-dimethylaminoethyl)amine and dimethyl sulfoxide (0.135 mL) were added to a 50 mL Schlenk round-bottom flask to prepare a solution, and the dissolved oxygen in the solvent was removed using the Schlenk anhydrous and oxygen-free technique. Transfer it into a syringe, set the injection pump flow rate to 0.01667ml / min, the reaction temperature to 40°C, and start the reaction. Due to the high flow rate, the pipeline was blocked and the injection pump alarmed, so the flow rate was changed to 0.00667mL / min, that is, the residence time was 150min. After 300min, the reaction solution was collected and quenched in liquid nitrogen. After the collection was completed, 90mL of cold methanol was added and allowed to stand for 2h, and the precipitate was separated by centrifugation. It was dissolved in tetrahydrofuran and separated again according to the above precipitation. Repeat the separation and purification steps for a total of three times, and the product was placed in a vacuum drying oven and dried for 48h. The enzyme-catalyzed ester exchange conversion rate was measured to be 89.39%, and the Cu(0)-catalyzed polymerization conversion rate was 46.02%. The obtained poly(trifluoroethyl acrylate)-poly(n-hexyl acrylate) copolymer (PTFEA 25 -co-PHA 70 ) has a number average molecular weight of 15570 g / mol, a molecular weight distribution index of 1.15, and a minute output of 0.0292 g / min.

[0104] Comparative Example 3

[0105] 0.6g of immobilized enzyme Novozyme435 with a particle size of 0.3-0.9mm was filled into a copper tube continuous flow microreactor with an inner diameter of 4.3mm after activation (retention volume 1.00mL). The pipeline was rinsed with toluene solvent after redispersion and drying. 9.632g (62.5mmol) of trifluoroethyl acrylate, 6.385g (62.5mmol) of n-hexanol, 0.061g (0.3125mmol) of ethyl 2-bromo-2-methylpropionate, 0.018g (0.078mmol) of tris(2-dimethylaminoethyl)amine and dimethyl sulfoxide (0.135mL) were added to a 50mL Schlenk round-bottom flask to make a solution, and the dissolved oxygen in the solvent was removed by Schlenk anhydrous and oxygen-free technology. It was transferred into a syringe and the injection pump flow rate was set to 0.016667mL / min, that is, the residence time was 60min. The reaction temperature was 40°C, the reaction was started, and the reaction solution was collected after 120 minutes. While collecting, it was quenched in liquid nitrogen. After the collection was completed, 90 mL of cold methanol was added and allowed to stand for 2 hours. The precipitate was separated by centrifugation, dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48 hours. The enzyme-catalyzed ester exchange conversion rate was measured to be 81.05%, and the Cu(0)-catalyzed polymerization conversion rate was 44.79%. The obtained poly(trifluoroethyl acrylate)-poly(n-hexyl acrylate) copolymer (PTFEA 15 -co-PHA 71 ) has a number average molecular weight of 12950 g / mol, a molecular weight distribution index of 1.22, and a minute output of 0.0404 g / min.

[0106] Comparative Example 4

[0107] 3.0g of immobilized enzyme Novozyme435 with a particle size of 0.3-0.9mm was filled into an activated copper tube microreactor with an inner diameter of 6mm (retained volume 5.00mL), and the two ends of the tube were fixed with a small amount of cotton. A microchannel tube with an inner diameter of 1mm was used to connect the syringe and the new microreactor (retained volume 0.5mL), and a microchannel reactor with an inner diameter of 1mm was used to connect the new microreactor and the receiving device (retained volume 0.5mL). The pipeline was rinsed with toluene solvent after redispersion and drying. In a 50mL Schlenk round-bottom flask, 62.5mmol (10.137g) benzyl acrylate, 62.5mmol (6.125g) furfuryl alcohol, 0.3125mmol (0.061g) ethyl 2-bromo-2-methylpropionate, 0.078mmol (0.018g) tris (2-dimethylaminoethyl) amine and dimethyl sulfoxide (2.05mL) were added to make a solution, and the dissolved oxygen in the solvent was removed by bubbling. It was transferred into the syringe of the injection device, and the flow rate was set to 0.083mL / min, that is, the residence time was 60min. The reaction temperature was 60℃, and the reaction was started. After 120min, the reaction solution was collected. While collecting, it was quenched in liquid nitrogen. After the collection was completed, 90mL of cold methanol was added and left to stand for 2h, and the precipitate was separated by centrifugation. It was dissolved in tetrahydrofuran and separated again according to the above precipitation. The separation and purification steps were repeated three times in total, and the product was placed in a vacuum drying oven and dried for 48h. The structure of the obtained polybenzyl acrylate-polyfurfuryl acrylate copolymer is 1 H NMR and GPC identification showed that the enzyme-catalyzed transesterification conversion rate was 6.07%, and the Cu(0)-catalyzed polymerization conversion rate was 48.44%. GPC determination showed that the polymer number average molecular weight was 7190 g / mol, and the molecular weight distribution index was 1.14.

[0108] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing functionalized polymers by continuous flow chemistry-enzymatic method, characterized in that: A mixed solution of acrylic acid ester monomers, an initiator, a ligand, a functional alcohol and a solvent is reacted in a microreactor to obtain a reaction solution containing functionalized polyacrylate.

2. The method according to claim 1, characterized in that: The microreactor is a copper tube, or a macro-microreactor containing copper internal components.

3. Application of a macro-microreactor in the preparation of functionalized polymers, characterized in that: A mixed solution of acrylic acid ester monomers, an initiator, a ligand, a functional alcohol and a solvent is reacted in a microreactor to obtain a reaction solution containing functionalized polyacrylate.

4. The method according to claim 1 or the use according to claim 3, characterized in that: The monomer includes a methacrylate monomer; the methacrylate monomer includes trifluoroethyl methacrylate, methyl methacrylate, or a combination of any of the foregoing; Preferably, the initiator comprises ethyl 2-chloropropionate, 2-bromopropionitrile, 2,2-dichloroacetophenone, methyl 2-chloropropionate, or any combination thereof; Preferably, the functional alcohol includes n-propanol, isopropanol, triethylene glycol monomethyl ether, 3-hydroxypropionitrile, or any combination thereof.

5. The method according to claim 1 or the use according to claim 3, characterized in that: The monomer is any one or a combination of trifluoroethyl acrylate, methyl acrylate, n-butyl acrylate, benzyl acrylate and cyclohexyl acrylate; Preferably, the initiator is any one or a combination of ethyl 2-bromo-2-methylpropionate, ethyl α-bromophenylacetate, diethyl 2-bromo-2-methylmalonate and ethylene glycol bromoisobutyrate; preferably, the molar ratio of the initiator to the monomer is 1:100-1000; Preferably, the ligand is tris(2-dimethylaminoethyl)amine and / or 4,4'-dinonyl-2,2'-bipyridine; preferably, the molar ratio of the initiator to the ligand is 1:0.1-1, preferably 1:0.25-0.5, and more preferably 1:0.25; preferably, the functional alcohol is any one or a combination of methanol, n-butanol, tert-butanol, n-hexanol, furfuryl alcohol, undecanol and 2-morpholineethanol; preferably, the molar ratio of the initiator to the functional alcohol is 1:100-1200; preferably, the solvent is any one or a combination of dimethyl sulfoxide, tetrahydrofuran, N,N-dimethylformamide and toluene, preferably dimethyl sulfoxide; preferably, the concentration of the monomer is 1-5 mol / L.

6. The method according to claim 2 or the use according to claim 3, characterized in that: The preparation method of the macro-microreactor is as follows: placing a copper spiral with a hollow center and an immobilized enzyme into a microchannel tube with an inner diameter of 2 to 4.3 mm; The retention volume of the macro-microreactor is 1-3 mL; the diameter of the copper spiral is 0.5-1 mm, and the pitch is 1-3 mm; the immobilized enzyme is immobilized lipase, preferably immobilized Novozymes 435 lipase.

7. The method according to claim 2 or the use according to claim 3, characterized in that: The preparation method of the macro-microreactor is as follows: placing a centrally hollowed copper internal component and an immobilized enzyme into a microchannel tube with an inner diameter of 2 to 15 mm; The retention volume of the macro-microreactor is 1 to 20 mL; the diameter of the copper internal component is 0.5 to 3 mm; preferably, the copper internal component is a spiral internal component, a serpentine internal component, an O-shaped internal component, or a linear internal component; the spiral internal component, the serpentine internal component and the O-shaped internal component have a pitch of 0.5 to 10 mm; the immobilized enzyme is any one or a combination of Candida antarctic lipase B, porcine pancreas lipase, Candida rugosa lipase, Amano Lipase from Pseudomonas fluorescens and lipase PS from Burkholderia cepacia.

8. The method according to claim 1 or the use according to claim 2, characterized in that: The mixed solution is reacted after removing dissolved oxygen; preferably, the method of removing dissolved oxygen is bubbling or liquid nitrogen freezing-vacuuming-dissolving.

9. The method according to claim 1 or the use according to claim 2, characterized in that: The reaction temperature is 0 to 100°C; preferably, the reaction rate is 0.0067 to 0.5 mL / min; preferably, the reaction retention time is 10 to 300 min, preferably 10 to 150 min; Preferably, after the reaction is completed, the reaction solution is quenched, an organic precipitant is added, and centrifuged to obtain a solid functionalized polyacrylate; preferably, the quenching agent is liquid nitrogen; preferably, the organic precipitant is a mixed solution of methanol and water, methanol, or n-hexane.

10. The method according to claim 1 or the use according to claim 2, characterized in that: The flow rate of the reaction is 0.0033-25 mL / min; preferably, the retention time of the reaction is 2-300 min.

Citation Information

Patent Citations

  • Method for realizing macroscopic transient assembly of hydrogel by utilizing enzymatic reaction and application

    CN113501914A

  • Method for preparing polyquaternium-51 through microjet mixer-microchannel reactor-tubular reactor

    CN115109188A

  • Method for preparing star-shaped block copolymer by using microreactor and application of star-shaped block copolymer

    CN116239734A

  • Reactive microparticles and use thereof for preparing functional hydrogel particles

    CN116829621A

  • Micro-liquid reaction vessel

    JP1986126450A

Cited By

  • Free radical polymerization method based on macro-micro reactor

    CN119954994A

  • A method for radical polymerization based on macro-microreactor

    CN119954994B